El rol de la familia y educación sexual de adolescentes de décimo año de la Unidad Educativa Manuel José Jaramillo, parroquia Casanga, en la actualidad. - Rodríguez Bravo, Stefany Gabriela (2024)
Sexual education focuses on providing adolescents with tools that allow them to make informed decisions. The general objective of this research was to analyze the family role and sexual education of tenth-year adolescents of the Manuel José Jaramillo Educational Unit, for which a bibliographic review was carried out through the collection and analysis of literature, and thus diagnose the role of the family and sexual education that students receive, finally an intervention proposal was made aimed at parents and adolescents. The research had a mixed approach, with techniques such as bibliographic review, the survey directed to 9 students and focus groups with 8 parents. As a result, it was determined that 22% of the students surveyed have assertive communication with their parents about sexual education, on the other hand, 88.8% of the students have limited knowledge about contraceptive methods, based on the findings the intervention proposal was designed in order to strengthen family communication about sexuality issues. It is concluded that there is a need to improve communication between parents and children, in addition to strengthening adolescents' knowledge about sexual education that allows them to make informed and responsible decisions.